Uncommon Imaging Findings of Inflammatory Myofibroblastic Tumor: Report of a Rare Case With Both Omentum and Mesentery Involvement in the Abdominal Cavity. (November 2018) - Fu, Hao; Guo, Xiuyu; Chen, Zijun; Wu, Hua; Chen, Haojun
Abstract : Abstract: The inflammatory myofibroblastic tumor (IMT) is a rare stromal tumor with diverse imaging findings. The present study describes a case of contrast-enhanced CT and 18 F-FDG PET/CT manifestations of an IMT with diffuse omental and mesenteric thickening and swelling in the entire abdominal cavity. It is extremely rare to observe such imaging features in the extrapulmonary IMT. Furthermore, this case emphasizes that 18 F-FDG PET/CT holds the potential for demonstrating IMT lesion extent and correctly identifying appropriate sites for biopsy.